Subcritical Water Extraction of Phenolic Compounds from Onion Skin Wastes (Allium cepa cv. Horcal): Effect of Temperature and Solvent Properties - Óscar Benito-Román; Beatriz Blanco; María Teresa Sanz; Sagrario Beltrán (MDPI AG, 2020)
The valorization of onion skin wastes (OSW) through the extraction, identification, and quantification of phenolic compounds was studied in this work, using subcritical water in a semicontinuous extractor (2.5 mL/min; 105-180 °C; 5 MPa). The extraction of flavonoids resulted to be fast (<30 min) and temperature sensitive (maximum at 145 °C; total flavonoids, 27.4 ± 0.9 mg/g dry OSW (DOSW)). The experimental results were fitted to the Weibull model. The influence of the solvent properties on the flavonoids quantification was found to be critical. A precipitate was formed once the extracts cooled down. If removed, a significant fraction of the high temperature extracted flavonoids (as much as 71%, at 180 °C) was lost. Such a condition affected especially those compounds that show extremely low solubility in water at room temperature, whereas quercetin glycosylated derivatives were less affected by the polarity change of the medium induced by the temperature change. It was demonstrated that it is necessary to re-dissolve the subcritical water extracts by the addition of ethanol, which led to a medium with a polarity equivalent to that obtained with water at high temperature. At 145 °C, quercetin (15.4 ± 0.4 mg/g DOSW) and quercetin-4'-glucoside (8.4 ± 0.1 mg/g DOSW) accounted for the 90% of the total flavonoids identified. By recovering high added value bioactive compounds from OSW the principles of circular economy were fulfilled, providing a new use for this agricultural waste.